Sign up ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Found these problems in a problem book and got stuck. The book doesn't have solutions to I've come here for help.

(1) Prove that for any integer $k>1$ and any positive integer $n$, there exist $n$ consecutive odd integers whose sum is $n^k$.

(2) Let $n$ be a positive integer and $m$ any integer of the same parity as $n$. Prove that there exist $n$ consecutive odd integers whose sum is $mn$.

share|cite|improve this question
What if $k=n=2$ ? Do we have $2$ consecutive integers whose sum is $2^2=4$ ? – lsp Feb 1 '14 at 9:26
odd integers @lsp 1+3 – Sameh Shenawy Feb 1 '14 at 9:31

2 Answers 2

$(1)$ $$\sum_{r=0}^{n-1}(2a+2r-1)=\frac n2\left[2a-1+2a+2(n-1)-1\right]=n(2a+n-2)$$

$$\implies 2a+n-2=n^{k-1}\iff 2(a-1)=n(n^{k-2}-1)$$ which is even for $k\ge2$ as then $n^{k-2}-1$ will be divisible by $n-1$

$(2)$ We need $n(2a+n-2)=mn\iff 2a+n-2=m\iff m-n=2a-2$ which is even $\implies m,n$ have same parity

share|cite|improve this answer
good answer, the q is : does such a exist for arbitrary k more than 1? – Sameh Shenawy Feb 1 '14 at 9:50
@Semsem, yes; we have $$a=1+\frac{n(n^{k-2}-1)}2$$ – lab bhattacharjee Feb 1 '14 at 9:52
i think you have to prove that it is an integer – Sameh Shenawy Feb 1 '14 at 9:54
@Semsem, for integer $k\ge2, (n-1)|(n^{k-2}-1)$ Now $n(n-1)$ is even, right? – lab bhattacharjee Feb 1 '14 at 9:55
yes it is +1 lab – Sameh Shenawy Feb 1 '14 at 9:58

Consider question part (1)

Without loss of generality, let $r$ denote an integer, so that the $n>0$ consecutive odd integers are

$(2r+1),(2r+3),...,(2r + 2(n-1))$

The sum of these integers is


This equals


The second (summation) term is a sum of odd numbers $1,3,..,(2n-1)$, which evaluates to $n^2$, because


Thus the sum of the $n$ consecutive numbers is

$S = 2rn+n^2=n(2r+n)$

To show that $S=n^k$ for integer $k>1$ it suffices to show that we can find integer $r$ such that


Rearranging we have

$\large r=\frac{n^{k-1}-n}{2}=\frac{n(n^{k-2}-1)}{2}$

The numerator of the RHS is always an even number for $k>1$, because if $n$ is even then $n^{k-2}$ is even as well, so that $n^{k-2}-1$ is odd, and the product of an even and odd number is even. Thus the RHS evaluates to an integer.

Conversely, if $n$ is odd, so is $n^{k-2}$, and $n^{k-2}-1$ is even, leading to the product of an even and odd number, which is even. Thus the RHS evaluates to an integer, so long as $k>1$.

Thus there exists integer $r$ such that $(2r+n)=n^{k-1}$, so that the sum of the $n$ consecutive numbers $S$ is $n^k$.

As for question part (2), recall that the sum of the $n$ consecutive integers (for intger $r,n$) is given by


Let us denote $m=(2r+n)$, then $m$ will be the same parity as $n$ as it equals $n$ plus an even number $2r$, so that


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.